Temperature Dependence of Thermodynamic Properties of Thallium Chloride and Thallium Bromide - Kavanoz, H. B. (WALTER DE GRUYTER GMBH, 2015)
Thermodynamic properties as lattice parameters, thermal expansion, heat capacities C-p and C-v, bulk modulus, and Gruneisen parameter of ionic halides TlCl and TlBr in solid and liquid phases were studied using classical molecular dynamics simulation (MD) with interionic Vashistha-Rahman (VR) model potential. In addition to the static and transport properties which have been previously reported by the author [13], this study further confirms that temperature dependence of the calculated thermophysical properties of TlCl and TlBr are in agreement with the available experimental data at both solid and liquid phases in terms of providing an alternative rigid ion potential. The results give a fairly good description of TlCl and TlBr in the temperature range 10-1000 K.
Keywords: thallium halides; thermophysical properties; molecular dynamics; BULK MODULUS; MOLECULAR-DYNAMICS; THERMAL-EXPANSION; STATIC STRUCTURE; IONIC TRANSPORT; COHESIVE ENERGY; HALIDES; PRESSURE; CRYSTALS; TLCL; Materials Science